Multiscale computing in systems medicine: a brief reflection - Zheng, Huiru; Talreja Wassan, Jyotsna; Alexandru Moisescu, Mihnea; Stoicu-Tivadar, Lacramioara; Miranda, João; Crisan-Vida, Mihaela; Stefan Sacala, Ioan; Badnjevic, Almir; CHorbev, Ivan; Jakimovski, Boro (IEEE, 2018)
Today’s modelling approaches in Systems Medicine are increasingly multiscale, containing two or more submodels, where each operates on different temporal and/or spatial scales. In addition, as these models become increasingly sophisticated, they tend to be run as multiscale computing applications using computational infrastructures such as clusters, supercomputers, grids or clouds. Constructing, validating and deploying such applications is far from trivial, and communities in different scientic disciplines have chosen very diverse approaches to address these challenges. Within this paper we reect on the use of Multiscale Computing within the context of Systems Medicine. Multiscale Computing is widely applied within this area, and instead of summarizing the eld as a whole we will highlight a set of challenges that we believe are of key relevance to the Systems Medicine community.
Keywords: Multiscale Computing; Systems Medicine; Ambient Assisted Living (AAL); Cloud Computing; Data Science; High Performance Computing (HPC); Internet of Things (IoT